The history and organization of the Workshop on Population and Speciation Genomics - Barth, Julia M I; Handley, Scott A; Kintzl, Daniel; Leonard, Guy; Malinsky, Milan; Matschiner, Michael; Meyer, Britta S; Salzburger, Walter; Stefka, Jan; Trucchi, Emiliano (Evolution, 2023)
With the advent of high-throughput genome sequencing, bioinformatics training has become essential for research in evolutionary biology and related fields. However, individual research groups are often not in the position to teach students about the most up-to-date methodology in the field. To fill this gap, extended bioinformatics courses have been developed by various institutions and provide intense training over the course of two or more weeks. Here, we describe our experience with the organization of a course in one of the longest-running extended bioinformatics series of workshops, the Evomics Workshop on Population and Speciation Genomics that takes place biennially in the UNESCO world heritage town of Český Krumlov, Czech Republic. We list the key ingredients that make this workshop successful in our view, explain the routine for workshop organization that we have optimized over the years, and describe the most important lessons that we have learned from it. We report the results of a survey conducted among past workshop participants that quantifies measures of effective teaching and provide examples of how the workshop setting has led to the cross-fertilisation of ideas and ultimately scientific progress. We expect that our account may be useful for other groups aiming to set up their own extended bioinformatics courses.
Keywords: Genomics; Course; Bioinformatics; Workshop; Education